PERANCANGAN AMBIENT MEDIA SEBAGAI MEDIA IKLAN LAYANAN MASYARAKAT BAHAYA ADIKSI INTERNET - Ade Moussadecq; Abdi Darmawan; Rohiman Rohiman (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2022)
The internet has both positive and negative effects on life. The positive impact of the internet is all the convenience in obtaining information, creating citizen journalism, social media and so on. But at the same time the massive internet growth also has negative impacts such as internet addiction (internet addiction). The purpose of research on Ambient Media (non-conventional advertising media) is related to the dangers of internet addiction as well as the brand positioning of the Darmajaya Institute of Informatics and Business. Institutions not only provide insight regarding information technology but also protect students from being negatively affected by information technology. This study uses a qualitative method, with a brainstorming approach that aims to generate ideas, spontaneity and creativity. The design process goes through the stages of drafting the concept, the process of designing sketches and continuing with the digitization of the sketch or the creation of ambient media designs. After that the process of designing the framework and continued with the formation of the body of the statue, the coloring of the statue and the final process of assembling the ambient media components. The results of this ambient media design research are a social media campaign tool for the community, especially students to avoid excessive behavior in using the internet that exceeds reasonable limits, as well as creating a visual appeal for the audience to receive social campaign messages